2002
DOI: 10.3171/jns.2002.97.5.1179
|View full text |Cite
|
Sign up to set email alerts
|

Transcorneal stimulation of trigeminal nerve afferents to increase cerebral blood flow in rats with cerebral vasospasm: a noninvasive method to activate the trigeminovascular reflex

Abstract: Data from the present study demonstrate that transcorneal stimulation of trigeminal nerve endings induces vasodilation and a robust increase in CBF. The vasodilatory response of cerebral vessels to trigeminal activation is retained after SAH-induced vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
(34 reference statements)
0
30
1
Order By: Relevance
“…The cerebrovascular sensory nerves originate in the trigeminal ganglion (Mayberg, Langer, Zervas, & Moskowitz, 1981). The electrical stimulation of the trigeminal ganglion (or its branches) causes an increase in the cerebral blood flow (Atalay et al, 2002;Lambert, Goadsby, Zagami, & Duckworth, 1988;Suzuki et al, 1990). It has been reported that trigeminal stimulation may improve the cerebral ischemic conditions such as cerebrovasospasm (Arbit & DiResta, 1996;Gurelik et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The cerebrovascular sensory nerves originate in the trigeminal ganglion (Mayberg, Langer, Zervas, & Moskowitz, 1981). The electrical stimulation of the trigeminal ganglion (or its branches) causes an increase in the cerebral blood flow (Atalay et al, 2002;Lambert, Goadsby, Zagami, & Duckworth, 1988;Suzuki et al, 1990). It has been reported that trigeminal stimulation may improve the cerebral ischemic conditions such as cerebrovasospasm (Arbit & DiResta, 1996;Gurelik et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the trigeminal ganglion is central to the cardiovascular adjustments associated with the mammalian diving reflex upon cold-water facial immersion (19), and releases known potent vasodilators, namely, substance P (309). In animals, trigeminal stimulation increases CBF (23,168,220,243,382). Similarly in humans, stimulation of the trigeminal ganglion by local injection of glycerol (451) or by thermocoagulation (450) yields marked increases in CBF.…”
Section: Neurogenic Regulation Of Cerebral Blood Flowmentioning
confidence: 99%
“…As well as nitrergic fibres, trigeminal sensory nerves that innervate pial vessels include a subpopulation of peptidergic fibres, some of which contain CCK, often co-localised with substance P or CGRP (Liu-Chen et al, 1985;O'Connor and van der Kooy, 1988). Antidromic activation of trigeminal afferents, either by stimulation of the trigeminal ganglion or via an axon reflex activated by stimulation of extracranial trigeminal sensory nerves, elicits vasodilatation in meningeal vessels (Atalay et al, 2002;Peitl et al, 2004). CCK released from trigeminovascular sensory nerve terminals could therefore contribute to this effect.…”
Section: Meningeal Vesselsmentioning
confidence: 98%